2004
DOI: 10.1038/sj.gene.6364116
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of the mannose-binding lectin (MBL2) gene reveals a high degree of heterozygosity with evidence of selection

Abstract: Human mannose-binding protein (MBL) is a component of innate immunity. To capture the common genetic variants of MBL2, we resequenced a 10.0 kb region that includes MBL2 in 102 individuals representing four major US ethnic groups. In all, 87 polymorphic sites were observed, indicating a high level of heterozygosity (total p ¼ 18.3 Â 10 À4 ). Estimates of linkage disequilibrium across MBL2 indicate that it is divided into two blocks, with a probable recombination hot spot in the 3 0 end. Three non-synonymous SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
2
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(105 citation statements)
references
References 113 publications
(112 reference statements)
7
88
2
6
Order By: Relevance
“…The g.388G4A, g.578G4A and g.797C4A variants were identified in another study, but without precise knowledge of the pattern of cooccurrence with another MBL2 variants (allelic haplotype). 30 The g.712A4T variant, found in our study with an overall frequency of 1.3%, was previously identified as g.712A4G (called -180A4G), with a 2% frequency in a sample of 24 Afro-Americans. 30 Allelic haplotypes under 'remarks' were thus defined in this study.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…The g.388G4A, g.578G4A and g.797C4A variants were identified in another study, but without precise knowledge of the pattern of cooccurrence with another MBL2 variants (allelic haplotype). 30 The g.712A4T variant, found in our study with an overall frequency of 1.3%, was previously identified as g.712A4G (called -180A4G), with a 2% frequency in a sample of 24 Afro-Americans. 30 Allelic haplotypes under 'remarks' were thus defined in this study.…”
Section: Resultssupporting
confidence: 49%
“…30 The g.712A4T variant, found in our study with an overall frequency of 1.3%, was previously identified as g.712A4G (called -180A4G), with a 2% frequency in a sample of 24 Afro-Americans. 30 Allelic haplotypes under 'remarks' were thus defined in this study. Amino-acid changes were deduced from sequence variations in bold.…”
Section: Resultssupporting
confidence: 49%
“…Recently, sequencing of a 10 kb region that includes the whole MBL2 gene (with introns) was performed in individuals representing four major American ethnic groups as well as a follow-up in Dutch Caucasians. 46,47 In total, 87 polymorphic sites were detected. These studies confirmed the strong preservation of the classical seven MBL2 haplotypes.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Although it is not certain whether these putative selective and counter balancing forces are operating in present day populations, sequence analysis of the extended MBL2 haplotypes of different US ethnic groups indicates a higher degree of heterozygosity than expected across the MBL2 gene, which indeed supports the notion that such forces are working even today. 46 So far, the putative selective forces have not been determined and may at this stage be regarded as hypotheses. Two assumptions are prevailing and both would confer survival advantages in response to infections in the reproductive age particularly in small children when innate immune mechanisms are relatively more important than adaptive immune mechanisms.…”
Section: Maintenance Of High Frequencies Of Mbl2 Variant Alleles In Dmentioning
confidence: 99%
“…5,6 Thus, it has been suggested that this variability confers relative advantages for the hostgenerally associated with heterozygosity-and represents a balanced genetic system. [7][8][9] The MBL2 concentrations are influenced by the allele '0' 10 in the first exon and, independently, by a number of nucleotide substitutions in the promoter region of the MBL2 gene. Particularly, a base pair substitution in codon À221 (G-C substitution), changing the promoter polymorphism from Y to X, has a profound downregulating effect on the serum MBL2 level.…”
Section: Introductionmentioning
confidence: 99%